Impact of high glucose and transforming growth factor-β on bioenergetic profiles in podocytes - Stieger, Nicole; Worthmann, Kirstin; Teng, Beina; Engeli, Stefan; Das, Anibh M.; Haller, Hermann; Schiffer, Mario (Metabolism-Clinical and Experimental, 2012)
Diabetic nephropathy is the most common cause of chronic renal failure in industrialized countries. Depletion of podocytes plays an important role in the progression of diabetic glomerulopathy. Various factors in the diabetic milieu lead to serious podocyte stress driving the cells toward cell cycle arrest (p27 Kip1), hypertrophy, detachment, and apoptosis. Mitochondria are responsible for oxidative phosphorylation and energy supply in podocytes. Recent studies indicated that mitochondrial dysfunction is a key factor in diabetic nephropathy. In the present study, we investigated metabolic profiles of podocytes under diabetic conditions. We examined oxygen consumption rates (OCRs) and oxidative phosphorylation complex activities in murine podocytes. Cells were exposed to high glucose for 48 hours, cultured for 10 passages under high-glucose conditions (30 mmol/L), or incubated with transforming growth factor-β (5 ng/mL) for 24 hours. After prolonged exposure to high glucose, podocytes showed a significantly increased OCR at baseline and also a higher OCR after addition of oligomycin, indicating significant changes in mitochondrial energy metabolism. Higher OCRs after inhibition of respiration by rotenone also indicated changes in nonmitochondrial respiration. Podocytes stimulated with a proapoptotic concentration of transforming growth factor-β displayed similar bioenergetic profiles, even with decreased citrate synthase activity. In all tested conditions, we found a higher cellular nicotinamide adenine dinucleotide content and changes in activities of respiratory chain complexes. In summary, we provide for the first time evidence that key factors of the diabetic milieu induce changes in glucose metabolism and mitochondrial function in podocytes. © 2012 Elsevier Inc. All rights reserved.
CRIS-Team Scopus Importer:2020-11-12